The Work of Code Switching: Implications for Gender and Racial Inequality in Employment - Krasas, Jackie (Religion & theology, 2018)
Although the term "code switching" arose in linguistic contexts, its meaning has broadened to include shifting the use of language, interactions, appearance, and the body in all areas of social life. Uncritical applications of the concept render invisible the normative nature and power dynamics along familiar dimensions of social inequality such as gender and race. "Whiteness" and "maleness" often become cast as the neutral standards against which all else is judged and are rarely revealed as the social constructions that they are. The result is the call for non-dominant groups to assimilate. In employment, we see this call for assimilation often under the guise of "soft skills," with particular reference made to the needs of a postindustrial service-oriented labor market. Cast in terms of skill, the heightened demand for code switching in employment promises to reproduce and even intensify existing labor market inequalities along the lines of gender and race.